La crisis del trabajo en la ciudad de León: de la restitución democrática al golpe de Estado (enero-julio de 1936) - Martínez Celada, José Luis (Estudios humanísticos. Geografía, historia y arte, 1999)
According to unemployment statistics, the Spanish Second Republic had to confront one of the hardest problems of this period, due to most of people would get involved in. The solutions from public institutions needed the support of private enterprises, whose primary purpose would be reduced the urban unemployment. From October 1934, the shocking truth would show other face. A critical social confrontation atmosphere broke down the weak compromise in order to solve this problem. The tension is clearly detectable from January to July 1936 in León. In the middle of it, the called "Elections of Frente Popular" turned more deep the social fracture. Thus, the town council had to head alone the battle against work-crisis in those seven months, although many troubles did not allow a satisfactory evolution of applied initiatives.